1999
DOI: 10.1088/0957-0233/10/12/316
|View full text |Cite
|
Sign up to set email alerts
|

The development of a light-collecting probe with high spatial resolution applicable to randomly fluctuating combustion fields

Abstract: A high-luminosity-light-collection system for highly spatial detection of chemiluminescence of radical species in flames has been developed. The system, multi-colour integrated Cassegrain receiving optics (MICRO) is based upon a Cassegrain-type configuration, which implies that it employs only reflective components (in combination with an optical fibre for light collection). It provides therefore spherical- and chromatic-aberration-free detection, which is of importance for high-spatial-resolution measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 16 publications
1
37
0
1
Order By: Relevance
“…It has been used for identification of the reaction zone [2], to compute Rayleigh index maps [3], as a marker of heat release rate [4][5][6], and to measure flame equivalence ratios [7][8][9][10][11][12]. By use of a Cassegrain optics-based Chemiluminescence Sensor (CS), similar to that used by Akamatsu et al [13] & Kojima et al [2], Hardalupas and Orain [7] demonstrated in their chemiluminescence study that the intensity ratio of the two excited radicals OH* and CH* is independent of strain rate in premixed counterflow flames at atmospheric pressure, in contrast to that of OH* and C 2 *, which is a function of strain rate.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used for identification of the reaction zone [2], to compute Rayleigh index maps [3], as a marker of heat release rate [4][5][6], and to measure flame equivalence ratios [7][8][9][10][11][12]. By use of a Cassegrain optics-based Chemiluminescence Sensor (CS), similar to that used by Akamatsu et al [13] & Kojima et al [2], Hardalupas and Orain [7] demonstrated in their chemiluminescence study that the intensity ratio of the two excited radicals OH* and CH* is independent of strain rate in premixed counterflow flames at atmospheric pressure, in contrast to that of OH* and C 2 *, which is a function of strain rate.…”
Section: Introductionmentioning
confidence: 99%
“…The spatially and temporally resolved detection system is a MICRO (Multi-colour Integrated Cassegrain Receiving Optics) system 33,34 , modified in previous studies 5,6 . The Cassegrain-based optical Sensor (CS) with the working distance of 300 mm had a primary and a secondary mirror of 150 and 50 mm diameters respectively, see Figure. 2.…”
Section: Spatially and Time Resolved Detection Systemmentioning
confidence: 99%
“…This ensured a probe volume of the sensor with nominal diameter of 200 µm and length of 1.6 mm 6 . There are two main advantages of the CS over the line of sight: one is avoiding chromatic aberrations for different wavelengths 33 , another is reducing the contribution of flame emissions from outside the probe volume 6,33 . The collected light from the CS was focused onto a pinhole placed in front of a UV-grade optical fibre (Thorlabs lnc, FT1500UMT), whose core diameter is 1500 µm and Numerical Aperture (NA) is 0.39.…”
Section: Spatially and Time Resolved Detection Systemmentioning
confidence: 99%
“…The single-lens optics has poor spatial resolution due to the spherical aberration and suffers from chromatic aberration in multi-wavelength-light measurements. In order to resolve these problems involved in single-lens optics, we developed a light-collection probe of Cassegrain type of a finite conjugate ratio named the Multi-color Integrated Cassegrain Receiving Optics (MICRO) (Akamatsu et al, 1999). The MICRO consists of an optimized pair of concave and convex mirrors and a light-detection unit connected by an optical fiber cable.…”
Section: Multi-color Integrated Cassegrain Receiving Optics (Micro) Fmentioning
confidence: 99%